2020
DOI: 10.7717/peerj.8551
|View full text |Cite
|
Sign up to set email alerts
|

Association between the levels of physical activity and plantar pressure in 6-14-year-old children

Abstract: Background The main purpose of the study was to determine whether lower levels of physical activity were associated with higher plantar pressure generated under each foot. Methods In this cross-sectional study, we recruited 641 children aged 6–14 years (agemean ± SD = 9.7  ± 2.4 years; heightmean ± SD = 143.6  ± 15.3 cm, weightmean ± SD = 37.6  ± 13.4 kg; body-mass indexmean ± SD = 17.6  ± 3.2 kg/m2; 44.2% girls). We used EMED –XL pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…There is a variability of foot structure and plantar pressure depending on age and type of determination (static or dynamic) [ 12 ], but also depending on the number of assessments according to age group [ 13 ] or the type and level of physical activity. In children and adolescents, a strong inverse correlation was reported between the plantar pressure and the level of physical activity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a variability of foot structure and plantar pressure depending on age and type of determination (static or dynamic) [ 12 ], but also depending on the number of assessments according to age group [ 13 ] or the type and level of physical activity. In children and adolescents, a strong inverse correlation was reported between the plantar pressure and the level of physical activity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 The changes in plantar pressure distribution cause losses in support and flexibility characteristics of the foot in functional activities such as walking, running, or standing. 8,9…”
Section: Introductionmentioning
confidence: 99%
“…7 The changes in plantar pressure distribution cause losses in support and flexibility characteristics of the foot in functional activities such as walking, running, or standing. 8,9 Plantar pressure assessment is one of the current measurements in understanding how body weight is transferred to the foot and to observe how the foot is shaped under load. 10,11 Some studies showed changes in both dynamic and static plantar pressures in functional changes in foot structure in obese children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…These changes are reflected in a decrease in speed and stride length, and an increase in the duration of the double phase of support, increased stride frequency, and reduced swing time (9,13). In children and adolescents, there is a strong inverse correlation between plantar pressure and physical activity levels (14,15). Assessment of plantar pressure may signal different postural changes in feet related to foot-level forces while standing and walking in both healthy subjects and various pathologies like obesity.…”
Section: Introductionmentioning
confidence: 99%